2015
DOI: 10.1002/jnr.23596
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of 14C‐labeled glucose metabolism by zinc during aluminium induced neurodegeneration

Abstract: Aluminium (Al) is one of the most prominent metals in the environment and is responsible for causing several neurological disorders, including Alzheimer's disease. On the other hand, zinc (Zn) is an essential micronutrient that is involved in regulating brain development and function. The present study investigates the protective potential of Zn in the uptake of (14) C-labeled amino acids and glucose and their turnover in rat brain slices during Al intoxication. Male Sprague Dawley rats (140-160 g) were divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…The reactions of the nervous system to aluminum intoxication are quite diverse. Neurotoxicity of aluminum may be accompanied by impaired glucose metabolism, cytoskeleton changes and modulation of signal transduction mechanisms (Singla et al, 2015). The studies in vivo and in vitro have shown that aluminum affects the formation of inositol phosphate.…”
Section: Introductionmentioning
confidence: 99%
“…The reactions of the nervous system to aluminum intoxication are quite diverse. Neurotoxicity of aluminum may be accompanied by impaired glucose metabolism, cytoskeleton changes and modulation of signal transduction mechanisms (Singla et al, 2015). The studies in vivo and in vitro have shown that aluminum affects the formation of inositol phosphate.…”
Section: Introductionmentioning
confidence: 99%